EFFECTS OF LABOR REALLOCATION ON PRODUCTIVITY AND INEQUALITY—INSIGHTS FROM STUDIES ON TRANSITION. (9th June 2016) - Tyrowicz, Joanna; van der Velde, Lucas; Svejnar, Jan
Abstract: From a theoretical perspective, the link between the speed and scope of rapid labor reallocation and productivity growth or income inequality is ambiguous. Do reallocations with more flows tend to produce higher productivity growth? Does such a link appear at the expense of higher income inequality? We explore the rich evidence from earlier studies on worker flows in the period of massive and rapid labor reallocation, that is, the economic transition from a centrally planned to a market‐oriented economy in CEE. We have collected over 450 estimates of job flows from the literature and used these inputs to estimate the short‐run and long‐run relationship between labor market flows, labor productivity, and income inequality. We apply the tools typical for a meta‐analysis to verify the empirical regularities between labor flows and productivity growth as well as income inequality. Our findings suggest only weak and short‐term links with productivity, driven predominantly by business cycles. However, data reveal a strong pattern for income inequality in the short run—more churning during reallocation is associated with a level effect toward increased Gini indices.